Therapeutic Potential of Metabotropic GABA (GABAB) Receptors and their Effector Ion Channels - Lujan, Rafael (Central Nervous System Agents in Medicinal Chemistry, 2007)
The discovery of metabotropic gamma-aminobutyric acid(B) (GABAB) receptors has enormously influenced our understanding of GABAergic neurotransmission in the central nervous system. These G-protein coupled receptors play critical roles in neuronal and glial functions, such as neuronal excitability and modulation of synaptic neurotransmission. Moreover they are involved in a variety of neurodegenerative and pathophysiological disorders, including epilepsy, spasticity, chronic pain, depression, schizophrenia, and drug addiction. GABAB receptor function is regulated by differences in expression and interactions with effector ion channels, mainly by inwardly rectifying K+ channels and voltagegated Ca2+ channels, and other signaling proteins on the neuronal surface. These receptors are widely expressed and distributed in the nervous system, being localized to both pre- and postsynaptic sites. Although GABAB receptors can be targeted to GABAergic synapses, they are mostly associated with glutamatergic synapses. Therefore, it is expected that this wide and heterogeneous distribution of GABAB receptors will open new opportunities for the development of pharmacological tools and new therapeutic strategies. Over the past decade, a number of agonists, antagonists and allosteric modulators selective for GABAB receptors have been developed. The combination of these pharmacological tools with genetic approaches is helping to elucidate the roles of GABAB receptors in the regulation of nervous system function in normal and pathological conditions. Moreover, these studies suggest that drugs active at GABAB receptors are interesting new targets to treat a wide variety of neurological and psychiatric disorders.
Keywords: neurological disorders